106k views
3 votes
What is the result of subtracting in the division problem shown below?

What is the result of subtracting in the division problem shown below?-example-1

2 Answers

7 votes

Answer:

The result is :
9x^(2) -6x-1

Explanation:

The given terms to be subtracted are ;


6x^(3)+x^(2) -10x-1 and


6x^(3)-8x^(2) -4x

So, subtracting each term to be more clear we get:


6x^(3)-6x^(3)=0


x^(2) -(-8x^(2) )=x^(2) +8x^(2) =9x^(2)


-10x-(-4x)=-10x+4x=-6x


-1+0=-1

So, the answer will be :


9x^(2) -6x-1

User Heavenly
by
5.2k points
1 vote

Answer:

The answer is 9x² - 6x - 1

Explanation:

∵ (6x³ + x² - 10x - 1) - (6x³ - 8x² - 4x) =

0 + 9x² - 6x - 1 = 9x² - 6x - 1

User Bobharley
by
5.4k points